Acceptability of transport pricing strategies - Schade, Jens; Schlag, Bernhard (Emerald, 2003)
Several studies and research projects all over the world have considered transport pricing strategies as promising attempts to solve the urgent traffic problems in urban areas. However, empirical results have shown that public and political acceptability of such strategies is low. Until now, acceptance research in transport has occurred in comparative isolation. There are no standardized terms and no generally recognized research methodologies. This volume attempts to overcome this research problem and bring the disciplines involved together. The first aim is a contribution to an interdisciplinary exchange which covers all relevant aspects of acceptance. Contributions come from some of the most recognized psychologists, economists, civil engineers, sociologists and political scientists in the field, including Bruno S. Frey, Tommy Gorling, Peter Jones, Jos Viegas, Tony May, Stef Proost, and other authors. The second aim is to look deeper into the question of which determinants influence the amount of acceptability. A third aim deals with chances to overcome the lack of public and political acceptability, to bring together the most advanced state of the art and to propose forthcoming and possible solutions for implementing different kinds of travel demand management measures including pricing. The book is based upon papers presented at the MC ICAM conference on Acceptability of Transport Pricing Strategies, held in Dresden, 23-24 May, 2002. It is divided into four parts, Setting the stage : acceptability problem, European research results, Behind public acceptability : relevant determinants, and Political acceptability, and tackles several relevant parts from a theoretical as well as from a practical viewpoint by asking questions like: how to explain the different levels of public acceptability of various travel demand management measures? Which factors influence the level of acceptability? How to deal with political acceptability problems? What should future implementation approaches look like from the point of view of acceptability?
Includes indexes.
Keywords: Transportation -- General.; Business & Economics -- Industries -- Transportation.; Transport industries.; Toll roads -- European Union countries -- Public opinion -- Congresses.; Automobile drivers -- European Union countries -- Attitudes -- Congresses.; Public opinion -- European Union countries -- Congresses.; Urban transportation policy -- European Union countries -- Congresses.; Congestion pricing -- European Union countries -- Congresses.; elektronické knihy; electronic books